Новый род жуков-щелкунов (Coleoptera, Elateridae) - Агаев, Б.И. (Вестник зоологии, 1985)
Idotarmonides gen. n. is established to include Betramon anatolicus Cd., 1881, that differs from all other genera of the tribe Pomachiliina by characters of antennae, pronotum and aedeagus. A key to relative Palearctic genera is given.